The interaction between popular economy, social movements and public policies: A case study of the waste pickers' movement - Angelique J.W.M. van Zeeland (United Nations Research Institute for Social Development (UNRISD), 2014)
This paper examines the challenges of expansion and sustainability of Social and Solidarity Economy (SSE). It focuses on the interaction between popular economy and SSE, and stresses the importance of collective action and public policies to enable the transition from the informal economy toward SSE. The main focus is on the waste pickers' movement. Experiences from Latin America, Asia and Africa show the possibilities of incorporating a significant contingent of informal waste pickers in solidarity economy organizations, but the scaling up of SSE raises challenges for sustainability. The first part addresses the challenge of formalization, regarding the approach between informal popular economy and SSE. The second part focuses on advocacy, claims making and policy influence of coalitions of community groups, social movements and non-governmental organizations (NGOs), examining the process of strengthening of national, regional and international movements of waste pickers, stressing the importance of participatory processes. The last part deals with the effective implementation of public policies through innovative institutional arrangements involving solidarity economy organizations in waste management systems. The cases demonstrate the potential of expanding SSE through collective action and effective public policies that support a process of social transformation. However, they also show the need for political conditions to ensure an enabling environment for SSE as well as the need to strengthen SSE through effective capacity building to meet the demands that arise as a result of the newly shaped public policies.
Keywords: 330